PENGARUH PENGETAHUAN PERPAJAKAN, KUALITAS PELAYANAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR KOTA BATAM - Kunthi Rahmawati; Ronald Wangdra (LPPM Universitas Putera Batam, 2025)
This research seeks to examine how tax knowledge, service quality, and tax penalties impact the compliance behavior of motor vehicle taxpayers in Batam City. Employing a quantitative approach, the study relies on primary data gathered through distributed questionnaires. A total of 118 individuals who pay motor vehicle taxes in Batam participated as respondents, with the sample size determined using Slovin's formula and finalized at 100 participants. The analysis was carried out using several statistical tools including tests for validity, reliability, normality, multicollinearity, and heteroscedasticity, along with multiple linear regression, coefficient of determination, significance testing, and the F test all conducted via SPSS software. The findings reveal that both tax knowledge and service quality significantly affect taxpayer compliance. In contrast, tax sanctions were found to have no meaningful effect on the compliance of motor vehicle taxpayers.